ANALISIS INVESTASI PORTFOLIO TERHADAP KEPUTUSAN PENGALOKASIAN DANA - Puspita, Maytaneel Wiga; Pratiwi, Ni Made Ida; Nasution, Ute Chairuz (Jurnal Dinamika Administrasi Bisnis, 2015)
Various reasons can influence decisions in the allocation of investment funds, one of which investment decisions in stock. By knowing the optimal stock portfolio can be obtained results of the most efficient investment and achieve the expected rate of return is greater. Single index method is one way to find out caru stocks efisein, by determining the ranking (order) stocks that have ERB (excess return to beta) highest to ERB (excess return to beta) is lower, so that it can be formed an investment portfolio of stocks that are most optimal when faced with two kinds of investments that produce the same returns two and two different risks, it would have been an investment with less risk, while when faced with two kinds of investments that generate two returns two different and the same risk, it would have been an investment with greater returns.Keywords:Â investment portfolio, single indexmethod, rate of return